Validation of the Italian version of Behavioral Pain Scale in sedated, intubated, and mechanically ventilated pediatric patients. - Guasconi, Massimo; Granata, Carlotta; Sulla, Francesco; Rubbi, Ivan; Artioli, Giovanna; Sarli, Leopoldo; Scelsi, Silvia (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Pain assessment in pediatric intensive care unit (PICU) is a demanding challenge. The COMFORT-B scale is recognized as the gold standard in such patients. However, the use of this instrument in PICU setting is disputed. The Behavioral Pain Scale (BPS), instead, is considered to be the gold standard for pain assessment in deeply sedated, mechanically ventilated adult patients. The BPS has been validated in Italian, requires a short observation time compared to the COMFORT-B and does not increase workloads. A first evaluation of BPS was made in PICU with good results regarding face validity and content validity, however suggesting further studies given the small sample on which it was tested. The aim of this study was the validation of the BPS in sedated, intubated, and mechanically ventilated pediatric patients.Methods: A descriptive, comparative design was used. A convenience sample of 84 non-verbal, sedated and mechanically ventilated critical care pediatric patients was included. Patient pain was assessed concurrently with three observational scales (BPS, COMFORT-B, NRS) before, during and after routine procedures that are considered painful and non-painful.Results: Internal consistency was α = .86. Correlations between BPS and the other instruments were high, demonstrating a good concurrent validity of the BPS. T test and assessment of ROC curves demonstrated a good discriminant validity of the BPS.Conclusions: The BPS proved to be valid and reliable for the assessment of pain also in the use with pediatric patients.